The Hypogeum of the Aurelii : a new interpretation as the collegiate tomb of professional scribae - Bradley, John W., (Archaeopress Roman archaeology ;, 2019)
This volume examines the frescoes of one of the most enigmatic funerary monuments of ancient Rome: the three chambers of the Hypogeum of the Aurelii. This study examines all the extant images in detail.